The profile of HIV/aids patients admitted with Deep Venous Thrombosis (DVT) at Nelson Mandela Hospital in Mthatha, South Africa - Olubanwo, Oludayo Olufemi (Stellenbosch : Stellenbosch University, 2017)
Thesis (MFamMed)--Stellenbosch University, 2010.